Microrna-668-3p mediates macrophage m2 polarization by targeting nfkbia to affect gastric cancer cell proliferation and migration - Chenghao Chu; Bin Liu; Yongwei Zhang; Zhangxuan Xu; Bin Wang; Kai Ling Chin (Researchgate, 2024)
Macrophage polarization is implicated in the pathological mechanism of gastric cancer (GC). This study investigated how the miR-668-3p/ Nuclear factor kappa B inhibitor alpha (NFKBIA) axis drives macrophage polarization to contribute to GC progression. Inhibitors or shRNA were used to interfere with the expression of miR-668-3p or NFKBIA in the GC cell line. Subsequently, CCK-8, EdU, wound healing, and transwell assays were used to assess the biological behavior of the GC cells. Bioinformatics analysis predicted the target connection between miR-668-3p and NFKBIA, and a dual luciferase reporter gene experiment confirmed this relationship. After THP-1 macrophages were co-cultured with the supernatant of transfected GC cells, the M1 and M2 macrophage phenotypes were determined. Subsequently, these THP-1 macrophages were co-cultured with GC cells using the Transwell, and the biological behaviors of the GC cells were determiend. miR-668-3p inhibitor suppressed proliferation, invasion and migration of GC cells. The phenotype of M1 macrophage (IL-1β, TNF-α and IL-6) was boosted yet the phenotype of M2 macrophage (CD206, Fizz1 and IL-10) was declined by miR-668-3p inhibitor. NFKBIA was the target gene of miR-668-3p and it reversed the effects of miR-668-3p inhibitor on macrophage polarization and biological behaviors of the GC cells.miR-668-3p suppressed NFKBIA in GC cells to mediate M2 polarization of macrophages, thereby facilitating the tumorigenesis of GC. Fullsize Image